Implementasi Pembatasan Akses Pemakai Komputer Menggunakan Group Policy Object Di Windows Server 2012 R2 - Marliana Sari (KILAT, 2017)
Network Security is a very important thing nowadays. Therefore organizations need to implement network security policies in their respective environments. One way to implement a network security policy is to limit user access by using the existing Active Directory GroupPolicy Object in Windows Server 2012 R2. By using Group Policy Object (GPO) in Windows Server 2012 R2, the administrator can apply the policy to the user or to the computer on the network.